UPAYA MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MATERI TEKNOLOGI PANGAN MELALUI MODEL PEMBELAJARAN RADEC DI KELAS 3 SD - Leny Vitriasari (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Critical thinking skills are one of the competencies that must be possessed by students in the 21st century. For this reason, teachers need to seek and improve critical thinking skills in learning so that students are accustomed and skilled in critical thinking and have the ability to think critically so that they can solve existing problems. Critical thinking skills can be grown through the RADEC learning model. This study aims to determine the extent to which the RADEC learning model can improve critical thinking skills for elementary school students. This qualitative research uses a descriptive method using data collection instruments using observation data collection methods through observation sheets of students' thinking skills data from the pretest and posttest of learning outcomes. The research subjects were 3rd grade elementary school students. From the results of this study, it shows that the RADEC Learning Model can improve students' skills to think critically, as seen from the percentage increase in each indicator of critical thinking with a significant change from the results of the pretest to the results of the post test.